The Role of Islamic Religious Extensions as Street-Level Bureaucrats in The Implementation of Islamic Community Guidance Policies in Batang Regency - Umi Kayatun; Aris Toening W; Permadi Mulajaya (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
This study aims to analyze the role of Islamic Religious Counselors as street-level bureaucrats in implementing Islamic Community Guidance policies in Batang Regency. The study used a mixed-methods approach with a sequential explanatory design, beginning with the collection and analysis of quantitative data and then deepening with qualitative data. Quantitative data were obtained from 53 respondents using a questionnaire that was tested for validity and reliability. In contrast, qualitative data were collected through in-depth interviews, observations, and documentation with religious counselors, Ministry of Religious Affairs officials, the KUA (Office of Religious Affairs), and the community. Data analysis was conducted descriptively and analytically using Michael Lipsky's street-level bureaucracy theory as an analytical framework. The study's results indicate that the role of Islamic Religious Extension Workers as street-level bureaucrats is positively and strongly associated with the successful implementation of the Islamic Community Guidance policy (r = 0.826; p < 0.01). Qualitative findings revealed that extension workers exercise discretion in the form of community assistance, adjustments to extension methods, strategic flexibility, and responsiveness to socio-religious issues at the local level. This study confirms that the effectiveness of Islamic Community Guidance policies is not determined solely by formal policy design but is highly dependent on the capacity, flexibility, and discretion of Islamic Religious Counselors, the implementing actors at the field level. These findings provide theoretical contributions to the development of street-level bureaucracy studies in the context of religious policy, as well as practical implications for formulating more contextual and responsive policies.